Video transmission to mobile phone - Ong, Magdalene Hui Shan. (2009)
In the context of today’s multimedia environment, there has been a growing need for multimedia service, wireless channels are characterized by varying bandwidth and bursty errors, compressed video is very sensitive to such error-prone transmission channels, video coding for mobile wireless transmission becomes a challenging task. Portable, battery-operated mobile devices are faced with constraints like battery life, memory size or bandwidth of communication link. Different video compression standards are specifically designed to cater for different individual applications. There is no one universal coding technique that can be applied to different kinds of applications. A possible means can thus be adapting the best available coding strategy to different portions of the data dynamically.